2015
DOI: 10.1021/acs.jmedchem.5b00828
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Molecular Therapeutics for Glaucoma: Challenges, Successes, and Promising Directions

Abstract: Glaucoma, a heterogeneous ocular disorder affecting ~60 million people worldwide, is characterized by painless neurodegeneration of retinal ganglion cells (RGCs), resulting in irreversible vision loss. Available therapies, which decrease the common causal risk factor of elevated intraocular pressure, delay, but cannot prevent, RGC death and blindness. Notably, it is changes in the anterior segment of the eye, particularly in the drainage of aqueous humor fluid, which are believed to bring about changes in pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 280 publications
(596 reference statements)
0
59
0
Order By: Relevance
“…al (Waki et al, 2001) first reported that Rho kinase inhibition could lower IOP in rabbits via topical application and intracameral injections of Y-27632. Following this initial observation, several laboratories have confirmed that Y-27632 and other Rho kinase inhibitors consistently lower IOP in various animal models including rabbits, rodents, cats and monkeys, under both normal and ocular hypertensive conditions (Donegan and Lieberman, 2016; Feng et al, 2015; Fukunaga et al, 2009; Inoue and Tanihara, 2013; Isobe et al, 2014; Junglas et al, 2012; Li et al, 2016; Nishio et al, 2009; Pattabiraman et al, 2015b; Sumi et al, 2014; Van de Velde et al, 2014). Importantly, both ROCK1 and ROCK2 null mice exhibit lower basal IOP, confirming a definitive role for Rho kinase in IOP homeostasis (Whitlock et al, 2009).…”
Section: Role Of Rho/rho Kinase Signaling In the Conventional Ah Omentioning
confidence: 86%
“…al (Waki et al, 2001) first reported that Rho kinase inhibition could lower IOP in rabbits via topical application and intracameral injections of Y-27632. Following this initial observation, several laboratories have confirmed that Y-27632 and other Rho kinase inhibitors consistently lower IOP in various animal models including rabbits, rodents, cats and monkeys, under both normal and ocular hypertensive conditions (Donegan and Lieberman, 2016; Feng et al, 2015; Fukunaga et al, 2009; Inoue and Tanihara, 2013; Isobe et al, 2014; Junglas et al, 2012; Li et al, 2016; Nishio et al, 2009; Pattabiraman et al, 2015b; Sumi et al, 2014; Van de Velde et al, 2014). Importantly, both ROCK1 and ROCK2 null mice exhibit lower basal IOP, confirming a definitive role for Rho kinase in IOP homeostasis (Whitlock et al, 2009).…”
Section: Role Of Rho/rho Kinase Signaling In the Conventional Ah Omentioning
confidence: 86%
“…A contributor to TM dysfunction is TM cell death, 24,43 which can be brought about by the aggregation of mutant myocilin. 44 Nonsynonymous mutations in myocilin, localized to its olfactomedin domain, result in non-native tertiary structures, which promote facile aggregation and leads to TM cell death. 43,45 Recently, it was demonstrated that Grp94 associates with amyloid-like aggregates of mutant myocilin but cannot triage these aggregates for degradation through the ER-associated degradation (ERAD) pathway.…”
Section: Primary Open Angle Glaucoma and Grp94-selective Inhibitionmentioning
confidence: 99%
“…Three of the 4 subtypes of ARs have been exploited with clinical candidate molecules for treatment of the eye: A 1 , A 2A , and A 3 . [43][44][45] Clinical trials for glaucoma have ensued. 46 The effects of AR modulation on specific tissues in the eye and on intraocular pressure (IOP) have been extensively probed by multiple techniques.…”
Section: Ocular Purine Receptors As Drug Targets 539mentioning
confidence: 99%